Impact of the transpulmonary pressure on right ventricle impairment incidence during acute respiratory distress syndrome: a pilot study in adults and children - Meryl Vedrenne-Cloquet; Matthieu Petit; Sonia Khirani; Cyril Charron; Diala Khraiche; Elena Panaioli; Mustafa Habib; Sylvain Renolleau; Brigitte Fauroux; Antoine Vieillard-Baron (Intensive Care Medicine Experimental, 2024)
Abstract Background Right ventricle impairment (RVI) is common during acute respiratory distress syndrome (ARDS) in adults and children, possibly mediated by the level of transpulmonary pressure (P L). We sought to investigate the impact of the level of P L on ARDS-associated right ventricle impairment (RVI). Methods Adults and children (> 72 h of life) were included in this two centers prospective study if they were ventilated for a new-onset ARDS or pediatric ARDS, without spontaneous breathing and contra-indication to esophageal catheter. Serial measures of static lung, chest wall, and respiratory mechanics were coupled to critical care echocardiography (CCE) for 3 days. Mixed-effect logistic regression models tested the impact of lung stress (ΔP L) along with age, lung injury severity, and carbon dioxide partial pressure, on RVI using two definitions: acute cor pulmonale (ACP), and RV dysfunction (RVD). ACP was defined as a dilated RV with septal dyskinesia; RVD was defined as a composite criterion using tricuspid annular plane systolic excursion, S wave velocity, and fractional area change. Results 46 patients were included (16 children, 30 adults) with 106 CCE (median of 2 CCE/patient). At day one, 19% of adults and 4/7 children > 1 year exhibited ACP, while 59% of adults and 44% of children exhibited RVD. In the entire population, ACP was present on 17/75 (23%) CCE. ACP was associated with an increased lung stress (mean ΔP L of 16.2 ± 6.6 cmH2O in ACP vs 11.3 ± 3.6 cmH2O, adjusted OR of 1.33, CI95% [1.11–1.59], p = 0.002) and being a child. RVD was present in 59/102 (58%) CCE and associated with lung stress. In children > 1 year, PEEP was significantly lower in case of ACP (9.3 [8.6; 10.0] cmH2O in ACP vs 15.0 [11.9; 16.3] cmH2O, p = 0.03). Conclusion Lung stress was associated with RVI in adults and children with ARDS, children being particularly susceptible to RVI. Trial registration Clinical trials identifier: NCT0418467.